Respuesta :

Answer:

[tex]\textsf{13)} \quad y=(x+5)^2+4[/tex]

[tex]\textsf{14)} \quad y=-\dfrac{1}{2}(x-2)^2-3[/tex]

Step-by-step explanation:

Vertex form of a parabola:  

[tex]y=a(x-h)^2+k[/tex]  where (h, k) is the vertex

Question 13

From inspection of the graph, the vertex is (-5, 4)

[tex]\implies y=a(x+5)^2+4[/tex]

To find [tex]a[/tex], substitute the coordinates of a point on the curve into the equation.

Using point (-4, 5):

[tex]\implies a(-4+5)^2+4=5[/tex]

[tex]\implies a(1)^2+4=5[/tex]

[tex]\implies a+4=5[/tex]

[tex]\implies a=1[/tex]

Therefore, the equation of the parabola in vertex form is:

[tex]y=(x+5)^2+4[/tex]

Question 14

From inspection of the graph, the vertex is (2, -3)

[tex]\implies y=a(x-2)^2-3[/tex]

To find [tex]a[/tex], substitute the coordinates of a point on the curve into the equation.

Using point (0, -5):

[tex]\implies a(0-2)^2-3=-5[/tex]

[tex]\implies a(-2)^2-3=-5[/tex]

[tex]\implies 4a-3=-5[/tex]

[tex]\implies 4a=-2[/tex]

[tex]\implies a=-\dfrac{1}{2}[/tex]

Therefore, the equation of the parabola in vertex form is:

[tex]\implies y=-\dfrac{1}{2}(x-2)^2-3[/tex]

#1

  • Vertex at (-5,4)

Equation

  • y=a(x+5)²+4

As there is no y inetercept present and the function is same as general quadratic equation y=x^2 just change in coordinates a=1

Final equation

  • y=(x+5)²+4

#2

  • Vertex (2,-3)

y=a(x-2)²-3

Use (4,-5)

  • -4=a(4-2)²-3
  • -1=a(2)²
  • 4a=-1
  • a=-1/4

Equation

  • y=-1/4(x-2)²-3